Produção de lipídios por Salicornia neei lag com potencial biotecnológico de aplicação para alimentos e meio ambiente. - Lima, Salatiel Henrique Pereira de (2023)
Salicornia has historically been used both in food and in other non-edible uses. The Oriental pharmacopoeia reports its medicinal uses. Salicornia neei Lag, a halophyte known as sea asparagus is found in temperate and subtropical salt marshes along the Atlantic coast of South America, grows in soils with high interstitial salinity (16 to 55 dS m-1). Investigations were conducted with Salicornia neei Lag aiming to locate and extract lipids from different parts of the plant (root, stem and leaf), in order to establish the profile of lipids and know the possible biotechnological applications, considering that the studies on lipids are mostly related to seed lipids. In this context, analyses were performed with the plant, and among these analyses, the histochemical method where the plant structure (root, stem and leaf) with higher lipid synthesis was located, being observed more intense coloration in the oil droplets present in the plant, which were stained black or dark blue. All structures showed lipid synthesis, but the highest amount of colored oil droplets were observed in the root. Total lipids were extracted with the solvent system chloroform: methanol (2:1, 1:1 and 1:2 v/v), showing higher values for the root, corresponding to 10.06%, followed by the leaf 5.67% and the stem 3.07%, confirming the results of histochemical localization. Continuing, studies were directed to evaluate the potential of root, stem and leaf oils in antimicrobial activity. The antimicrobial activity of the lipids isolated from the root, leaf, and stem showed preferential action against fungi. However, the lipids from the stem showed activity against Pseudomonas aeruginosa UCP 1559 and from the leaf against Bacillus subtilis UCP 1593, respectively, indicating high potential of both for the pharmaceutical area, generating prospects of applicability as a candidate for the pharmaceutical area. And the viscosity of the root, stem and leaf oils were also evaluated, the results of the viscosities were very promising, demonstrating the high potential for application in the development of hybrid biofuels, representing for root values of 71.4%, stem 85.9% and leaf 76.30%. The promising results of the studies performed with the oils from S. neei, generated promising perspectives in the development and innovation from the halophytes plant, where two patents were filed.